Challenges of Implementing Sex Education in Millennial Families to Anticipate Sexual Violence Against Children in Makassar - Anjasmira, Evi Irdawanti; Manda, Darman; Awaru, A. Octamaya Tenri; Nur, Hasruddin; Najamuddin, Najamuddin (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2025)
Sexual education is the process of providing information, understanding to children about aspects of reproductive sexual health, relationships, behavior and responsibility. Families should play a role in providing socialization of sexual education to children. However, the fact is that parents since ancient times have really considered taboo anything that smells of the word sex including providing sexual education to children. The reality in the field shows that the level of sexual violence that occurs to children in Indonesia is increasing every year including in Makassar, This study uses a descriptive qualitative research method. The data collection technique is by conducting observations, interviews and documentation. The results of this study indicate that the challenges faced by millennial parents in providing sexual education to children are. The influence of social media, dependence on uncurated online information, social stigma that still exists, Gaps in inclusive or open teaching and Cultural and religious resistance. These challenges affect the effectiveness of delivering sexual education in the family, which in the end can have an impact on children's understanding of incorrect sexuality issues.